Exploring Trends and Gaps in Teaching Linguistics Research among Undergraduate EFL Students: A Bibliometric Analysis - Rohima Nur Aziza Al Hakim (REiLA)
The importance of linguistics is not just for EFL teachers to assist in mastering the concept of teaching. However, the understanding of linguistics should be started with the introductory for EFL Students as a fundamental course to help them build their understanding regarding what they are studying including the trends and gaps of the study in that context. This study aims to analyse trends and gaps in studies regarding teaching linguistics as a subject taught to EFL Students at the university level. This qualitative research applied bibliometrics analysis by collecting relevant studies taken from Publish or Perish and manage to collect 599 articles related to teaching linguistics from Google Scholar, Scopus, and Web of Science databases ranging from 2018-2022; by applying exclusion and inclusion criteria, 367 articles were selected to be analysed using VOSviewer. The result showed the terms for the classroom, technology, foreign language, type, attitude, and literature are the most frequent and mostly discussed by the researchers. While in terms of solution, exploration, contribution, learning process, perception, difficulty, and text seems still gaining less attention compare the others. Therefore, these spots can be seen as research topic opportunity for future researchers to finding the niche. These result implies and also highlights that there are still many interesting topic to be explored regarding the scope of linguistics in language learning.